2019
DOI: 10.3389/fvets.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Application and Resistance in Swine Production in China: Current Situation and Future Perspectives

Abstract: To meet increasing demand for animal protein, swine have been raised in large Chinese farms widely, using antibiotics as growth promoter. However, improper use of antibiotics has caused serious environmental and health risks, in particular Antimicrobial resistance (AMR). This paper reviews the consumption of antibiotics in swine production as well as AMR and the development of novel antibiotics or alternatives in China. The estimated application of antibiotics in animal production in China accounted for about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 100 publications
1
59
0
1
Order By: Relevance
“…We found most of the S . Rissen isolates showed resistance to tetracycline, streptomycin, trimethoprim-sulfamethoxazole, chloramphenicol, sulfisoxazole, and ampicillin ( Figure 2 ) which correlates well with other studies and could be linked with the findings that the antimicrobials were commonly used in swine farms in China [ 42 , 43 ]. Tetracycline is one of the most commonly used antimicrobial agents in humans, as well as in veterinary medicine, and is also one of the most extensively used drugs in animal husbandry in China and many other nations.…”
Section: Resultssupporting
confidence: 87%
“…We found most of the S . Rissen isolates showed resistance to tetracycline, streptomycin, trimethoprim-sulfamethoxazole, chloramphenicol, sulfisoxazole, and ampicillin ( Figure 2 ) which correlates well with other studies and could be linked with the findings that the antimicrobials were commonly used in swine farms in China [ 42 , 43 ]. Tetracycline is one of the most commonly used antimicrobial agents in humans, as well as in veterinary medicine, and is also one of the most extensively used drugs in animal husbandry in China and many other nations.…”
Section: Resultssupporting
confidence: 87%
“…Currently, the presence and the dissemination of AMR among the genus Escherichia spp. represents an emerging problem (56,57). In the present study, Stx2e-producing isolates isolated from farmed pigs showed high levels of resistance to various antimicrobial agents.…”
Section: Discussionmentioning
confidence: 54%
“…Antimicrobial resistance (AMR) has become a major public health concern because bacteria causing infectious diseases are becoming less susceptible to antibiotic treatment (56,57). However, antibiotic resistance can also arise in opportunistic bacteria, such as E. coli, as a result of different mechanisms (56).…”
Section: Discussionmentioning
confidence: 99%
“…However, antibiotics are still in use as growth promoters in some countries outside the EU. China has not yet prohibited the use of antibiotics as growth promoters, however they are proposing restrictions [ 89 , 90 ], similar to the FDA in the USA.…”
Section: Use Of β-Lactam Antibiotics In Pig Productionmentioning
confidence: 99%